Assessing the readiness of dental students in providing Dental Health Education (DHE) regarding sugar: a pilot study / Nawwal Alwani Mohd Radzi … [et al.] - Mohd Radzi, Nawwal Alwani; Azizan, Nur Diyana; Adnan, Sara Yasmin; Md Bohari, Nor Faezah; Bakri, Noor Nazahiah (2019)
This study assessed dental students’ readiness in giving information about dietary sugar intake and the effectiveness of the intervention in increasing their knowledge when giving sugar-related advice to patients. Materials and Methods: 176 dental students from Faculty of Dentistry, Universiti Teknologi MARA (UiTM) participated in this study. A self-administered questionnaire was administered to Year 3, 4 and 5 dental students in the classroom that assessed their basic knowledge and perceived readiness in educating patients regarding sugar before and after the intervention. The interventions were inclusive of a handheld brochure and a 90-second video projection regarding hidden sugars, recommended daily sugar intake and how to identify sugar content on food labels. Results: The students’ basic knowledge regarding sugar and their perceived readiness were significantly improved following the intervention. The mean scores for baseline was 5.69, (SD = 1.331) and post-intervention score was 9.87, (SD= 0.355), p value < 0.05 and 95% CI. The score remains higher than the baseline 4 weeks after the intervention with 9.04 (SD= 0.858), p value < 0.05 and 95% CI. Conclusion: The intervention improved the students’ knowledge in delivering sugar-related advices and some aspects of food label literacy regarding sugar. This will facilitate and empower the students to deliver consistent and practical messages about sugar with regards to oral and general health to their patients.